Answer:
![\displaystyle 6x - y = -15, -6x + y = 15, or\:y = 6x + 15](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3of1wtp2xf2gz0txmouvhkc20g2my1tyo4.png)
Explanation:
First, find the rate of change [slope]:
![\displaystyle (-y_1 + y_2)/(-x_1 + x_2) = m \\ \\ (0 - 12)/(0 - 2) = (-12)/(-2) = 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1wqompbgu1zw0yk3kvzim7x1yr0yalco3d.png)
Then plug [−1, 9] into the Slope-Intercept Formula instead of the Point-Slope Formula because you get it done much more swiftly:
9 = 6[−1] + b
−6
![\displaystyle 15 = b \\ \\ y = 6x + 15](https://img.qammunity.org/2020/formulas/mathematics/middle-school/25z1jbxgm31cebabshr2iff292e9rozpdk.png)
If you want it in Standard Form:
y = 6x + 15
- 6x - 6x
__________
![\displaystyle -6x + y = 15\:OR\:6x - y = -15](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ewoa20rwchj5vcyqotm7am22hafrkguojc.png)
I am joyous to assist you anytime.